Emotional Intelligence and Its Relationship with Emotional Well-Being and Academic Performance: The Vision of High School Students - María Dolores Toscano-Hermoso; Carlos Ruiz-Frutos; Javier Fagundo-Rivera; Juan Gómez-Salgado; Juan Jesús García-Iglesias; Macarena Romero-Martín (MDPI AG, 2020)
Emotional intelligence skills in students may be related with physical and mental health, within and outside the academic field. Strengthening these skills can lead to greater overall well-being, lower use of substances, and improved academic performance, as well as reduced aggressive behaviours. The objective of this study was to analyse the levels of emotional intelligence (differentiating between the dimensions: emotional Attention, Clarity, and Repair) among high school students and examine its relationship with academic performance and emotional well-being, considering if there are differences between boys and girls and between different grades. A cross-sectional descriptive study was developed on a sample of 333 High School students using the Trait Meta-Mood Scale (TMMS) and KIDSCREEN-10 Index tools. Differences in emotional intelligence were observed between boys and girls for the three dimensions, and a relationship between emotional intelligence and student well-being was appreciated. No relationships were found between emotional intelligence and academic performance, nor have any differences been observed between the different courses analysed. It cannot be concluded that academic performance is related to emotional intelligence, but a relationship between well-being and emotional intelligence is found.